Las encuestas electorales no son una bola de cristal (2010)
ABSTRACT: The opinion polls "do not predict" anything. They portray the state of situation of the moment at which the interviews became. Between that moment and the day of the elections or the moment of the next survey the opinions can vary by virtue of diverse circumstances. The opinion surveys look for to interpret a present reality of which it is possible to be inferred what could happen next in the future. The function of the survey is to portray a little while certain reality of and indicating tendencies." the use of the survey on the part of mass media has taken it to be located like a "crystal ball" when its function is a description element, not of prediction.